Synthesis of Diazepine-fused Porphyrinoids and Annulated Porphyrin Arrays - SENGE, MATHIAS (My University, 2014)
Porphyrins with exocyclic rings allow for significant modulation of the photochemical properties of the macrocycle via modulation of the aromatic system through electronic and conformational effects. Here we sought to generate such porphyrinoids via a stepwise strategy involving two cycloaddition steps, the first improving the synthesis of a relatively unstable dehydropurpurin intermediate which ring opens to form a key 1,5-diketone species. A library of a new class of porphyrinoids, namely diazepine-fused porphyrinoids was synthesized via condensation methods from these 1,5-diketone precursors in yields of 8-49 %. Cycloaddition methodologies were also applied to bisporphyrins and their reactivities were investigated
PUBLISHED
Keywords: Porphyrinoids, Cycloaddition, Diazepine, 1,5-Diketones; Porphyrinoids, Cycloaddition, Diazepine, 1,5-Diketones